1980
DOI: 10.1142/s0192415x80000153
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Relief by Transcutaneous Electrical Nerve Stimulation (TENS)

Abstract: In prospective, random assignment of 2 groups of 15 patients, relief of postoperative pain with narcotic medications was evaluated and compared with transcutaneous electrical nerve stimulation (TENS) for 2 days immediately following surgery. Presence of ileus and hospital stay were identical in both groups. Patients on TENS demonstrated a marked significant decrease in the amount of narcotics administered. There was favorable nursing, physician and patient acceptance to these devices. Further clinical evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Two out of 17 studies compared different frequencies of stimulation [45, 47], and 1/17 compared EA with manual acupuncture [21]. In the 17 peri-incisional stimulation studies, 11 compared with sham [24, 30, 32, 33, 3638, 43, 50, 51, 54], three compared with non-active stimulation [23, 25, 52], and three compared with both [31, 39, 53]. In addition, one study compared different intensities of stimulation [30], and one compared different frequencies of stimulation [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two out of 17 studies compared different frequencies of stimulation [45, 47], and 1/17 compared EA with manual acupuncture [21]. In the 17 peri-incisional stimulation studies, 11 compared with sham [24, 30, 32, 33, 3638, 43, 50, 51, 54], three compared with non-active stimulation [23, 25, 52], and three compared with both [31, 39, 53]. In addition, one study compared different intensities of stimulation [30], and one compared different frequencies of stimulation [32].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies in distal group and one study in peri-incisional group reported side effects associated with the treatment [32, 35, 50, 52]. Side effects included erythema due to Capsicum plaster, a tingling and transient warm sensation, restricting activities and discomfort influencing sleep quality due to electrodes and wires.…”
Section: Resultsmentioning
confidence: 99%
“…Of the seven studies, GI recovery following stimulation was a primary outcome in four studies . The remaining three studies primarily focused on the use of TENS for controlling postoperative pain and reported secondary effects on the GI system . Pain scores were reported in all studies as a primary or secondary outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Pain scores were reported in all studies as a primary or secondary outcome. Quantitative analysis of opiate reduction was only reported in two studies , which demonstrated a 3× reduction , and 30× reduction , in total opiates used.…”
Section: Resultsmentioning
confidence: 99%
“…[12] Sodipo et al . [13] proved that for patients given TENS along with narcotics immediately after surgery, there is a marked significant decrease in the amount of narcotics administered. There was favorable nursing, physician and patient acceptance to these devices.…”
Section: Discussionmentioning
confidence: 99%